Modifikasi Pembuatan Garam Industri Dari Air Laut Dengan Metode Pengendapan - Mikrofiltrasi - Elysia, Alvina; Sanjaya, Denny; Widayat, W; Kusmiyati, K (Pusat Kajian Halal Undip, 2021)
Garam adalah komponen yang sering digunakan untuk konsumsi maupun bahan baku industri. Garam mengandung banyak impuritas seperti MgCl2, MgSO4, CaCl2, dan Na2SO4 sehingga perlu dicari proses untuk menghilangkan impuritas tersebut guna meningkatkan kadar NaCl. Penelitian ini bertujuan untuk mempelajari proses peningkatan kadar NaCl dengan mengendapkan impuritas dan mencari kondisi operasi optimum dalam proses pengendapan magnesium stearat dan kalsium stearat. Proses pengendapan ion Ca2+ dan Mg2+ dilakukan pada variabel suhu 80 oC dan 90 oC serta variabel konsentrasi Natrium Stearat 5 %V dan 10 %V. Untuk optimasi, percobaan dilakukan dengan Central Composite Design. Asam Stearat direaksikan dengan NaOH untuk menghasilkan Natrium Stearat (CH3(CH2)16COONa). Larutan Natrium Stearat ini dicampurkan dengan air garam sehingga menimbulkan endapan putih yang merupakan campuran Kalsium Stearat dan Magnesium Stearat. Model persamaan pengendapan Ca2+ adalah Y = 191,185 + 5,206 XK - 0,072 XK2 - 3,687 XT + 0,026XT2 - 0,036 XKXT dengan yield (Y) optimum 77,558. Model persamaan pengendapan Mg2+ adalah Y = 78,722 + 2,525XK - 0,027 XK2 + 0,319XT - 0,001XT2 - 0,023XKXT dengan yield optimum 97,361. Model persamaan pengendapan NaCl adalah Y = -991,238 + 16,582 XK - 0,153 XK2 + 24,007XT - 0,135XT2 - 0,154 XKXT dengan kadar optimum 95,536 %. Hasil ini belum memenuhi SNI garam industri yaitu kadar NaCl sebesar 98,5 %. Dengan demikian, proses ini belum cukup aplikatif untuk menghasilkan garam industri sesuai SNI. Kata kunci : Central composite design, impuritas, NaCl, , natrium stearat Abstract MODIFICATION ON INDUSTRIAL SALT PRODUCTION VIA PRECIPITATION METHOD – MICROFILTRATION. Salt is a component frequently used for consumption and raw material in industries. Salt contains many impurities such as MgCl2, MgSO4, CaCl2, and Na2SO4, hence a process is imperative to remove the impurities to increase the NaCl content. This research aims to study the process on increasing NaCl content by precipitating the impurity and finding the optimal operation condition in the precipitation process of magnesius stearate and calcium stearate. The precipitation process of Ca2+ and Mg2+ ions are carried out on temperature variables of 80 oC and 90 oC along with the concentration variable of 5 %V and 10%V sodium stearate. Optimization was carried out using the Central Composite Design. Stearic acid was reacted with NaOH to produce sodium stearate (CH3(CH2)16COONa). The sodium stearate micture was mixed with salt water to produce white precipitate containing calcium stearate and magnesium stearate mixture. The model equation of the Ca2+ precipitation was Y = 191.185 + 5.206 XK – 0.072 XK2 – 3.687 XT + 0.026XT2 – 0.036 XKXT with optimum yield (Y) 77.558. Meanwhile, the model equation of the Mg2+ precipitation was Y = 78.722 + 2.525XK – 0.027 XK2 + 0.319XT – 0.001XT2 – 0.023XKXT with optimum yield 97.361. The model equation of the NaCl precipitation was Y = -991.238 + 16.582 XK – 0.153 XK2 + 24.007XT – 0.135XT2 – 0.154 XKXT with an optimum content of 95.536%. The obtained result has not meet the Indonesian National Standard for NaCl content in industrial salt which was 98.5%. Therefore, this process was not yet applicable enough to produce industrial salt with Indonesian National Standard. Keywords: Central composite design, impurity, NaCl, sodium stearate